Probiotic Potential of Enterococcus faecium Isolated from Chicken Cecum with Immunomodulating Activity and Promoting Longevity in Caenorhabditis elegans - sim, Insuk; Park, Keun-Tae; Kwon, Gayeung; Koh, Jong-Ho; Lim, Young-Hee (Journal of microbiology and biotechnology, 2018)
Probiotics, including , confer a health benefit on the host. An strain was isolated from healthy chicken cecum, identified as by 16S rDNA gene sequence analysis, and designated as L11. To evaluate the potential of L11 as a probiotic, the gastrointestinal tolerance, immunomodulatory activity, and lifespan extension properties of the strain were assayed. L11 showed >66% and >62% survival in artificial gastric juice (0.3% pepsin, pH 2.5) and simulated small intestinal juice (0.5% bile salt and 0.1% pancreatin), respectively. Heat-killed L11 significantly ( < 0.05) increased immune cell proliferation compared with controls, and stimulated the production of cytokines (IL-6 and TNF-α) by activated macrophages obtained from ICR mice. In addition, L11 showed a protective effect against Typhimurium infection in . In addition, feeding L11 significantly ( < 0.05) extended the lifespan of compared with the control. Furthermore, genes related to aging and host defense were upregulated in L11-fed worms. In conclusion, L11, which prolongs the lifespan of , may be a potent probiotic supplement for livestock.